Dielectric properties of the system: 4-n-pentyloxybenzoic acid– N-(4-n-butyloxybenzylidene)-4᾽-methylaniline - S. A. Syrbu; M. S. Fedorov; E. A. Lapykina; V. V. Novikov (Тонкие химические технологии, 2021)
Objectives. Our aim was to study the dielectric properties of the 4-n-pentyloxybenzoic acid– N-(4-n-butyloxybenzylidene)-4’-methylaniline system and reveal how different concentrations of N-(4-n-butyloxybenzylidene)-4’-methylaniline additives affect the dielectric properties of 4-n-pentyloxybenzoic acid.Methods. System properties were investigated using polarization thermomicroscopy and dielcometry.Results. We found that dielectric anisotropy changes its sign from positive to negative at the transition temperature of the high-temperature nematic subphase to the low-temperature one. The anisotropy of the dielectric constant of N-4-n-butoxybenzylidene-4’-methylaniline has a positive value and increases as to the system approaches the crystalline phase. The crystal structure of the 4-n-pentyloxybenzoic acid contains dimers formed by two independent molecules due to a pair of hydrogen bonds. The crystal structure of N-(4-n-butoxybenzylidene)-4’-methylaniline contains associates formed by orientational interactions of two independent molecules. 4-n-Pentyloxybenzoic acid dimers (270 nm) and associates of N-4-n-butoxybenzylidene-4’- methylaniline (250 nm) proved to have approximately the identical length. Considering the close length values of the structural units of both compounds and the dielectric anisotropy sign, we assume that the N-4-n-butoxybenzylidene-4’-methylaniline associates are incorporated into the supramolecular structure of the 4-n-pentyloxybenzoic acid. The specific electrical conductivity of the compounds under study lies between 10−7 and 10−12 S∙cm−1. The relationship between the specific electrical conductivity anisotropy and the system composition in the nematic phase at the identical reduced temperature, obtained between 100 and 1000 Hz is symbatic. However, the electrical conductivity anisotropy values of the system obtained at 1000 Hz are lower compared to those obtained at 100 Hz. At N-(4-n-butoxybenzylidene)-4’-methylaniline concentrations between 30 and 60 mol %, the electrical conductivity anisotropy values are higher than those of the individual component.Conclusions. A change in the sign of the dielectric constant anisotropy of the 4-n-pentyloxybenzoic acid during nematic subphase transitions was established. We showed that the system has the highest dielectric constant anisotropy value when components have an equal number of moles. Highest electrical conductivity anisotropy values are observed when the concentration of the N-4-n-butoxybenzylidene-4᾽-methylaniline system lies between 30 and 60 mol %.